The effectiveness and cost of lansoprazole and pantoprazole for stress ulcer prophylaxis in intensive care unit - Mega Octavia; Zullies Ikawati; Tri Murti Andayani (Universitas Ahmad Dahlan, 2021)
The incidence of bleeding is increased in high risk patients with critical conditions in Intensive Care Unit (ICU). Appropriate prophylaxis medicine is necessary to reduce the incidence of stress ulcer bleeding during hospitalization in ICU which further can minimize the cost of patient care in the ICU. Currently, lansoprazole and pantoprazole are used as a stress ulcers prophylaxis. Nevertheless, there has not been sufficient evidence proving their effectiveness. This study was aimed to compare the effectiveness and cost between iv lansoprazole and iv pantoprazole as a stress ulcer prophylaxis in ICU. In this retrospective observational study, the data were obtained from medical records of all patients admitted to ICU in a District Hospital in Yogyakarta from January 2014 until December 2016. Effectiveness of therapy were obtained from objective data in the medical record by looking at the incidence of major (clinically signiï¬cant) and minor (overt gastrointestinal) bleeding. Chi-square analysis was performed to analyze the difference of bleeding incidence. The average cost was presented as Expected Monetary Value (EMV), which consisted of the cost of prophylaxis and treatment of bleeding. The difference in average cost was analyzed using independent t-test. A total of 119 patients were included in this study. There were 62 patients in the lansoprazole group and 47 patients in the pantoprazole group. Forty eight patients (77,4%) from lansoprazole group and 35 patients (61,4%) from pantoprazole group did not experience any GI bleeding. There was no statistical difference in the incidence of GI bleeding between the two groups (CI 95%, P-value = 0.057). The EMV of lansoprazole group was higher than pantoprazole group IDR 645.122,57 and IDR 511.629,39 respectively. In conclusion, there was no significant difference regarding the effectiveness between iv lansoprazole and iv pantoprazole as stress ulcer prophylaxis. Costs for the prophylaxis of stress ulcers is lower on the use of pantoprazole compared to lansoprazole.